Ecological Dynamics and Management of Citrus Psylla Diaphorina citri Kuwayama (Hemiptera: Psyllidae) Under Semi-arid Conditions in India - Mandeep Pathania; Arti Verma; Parshotam Kumar Arora; Shashi Pathania; Nirmaljit Kaur (Applied Fruit Science, 2026)

Exploring water-ice deposits in lunar polar craters with Chandrayaan-2 DFSAR data - Nidhi Verma; Megha Bhatt; Mayand Dangi; Shashi Kumar; Anil Bhardwaj (Icarus, 2025)

Overexpression of miR166 in Response to Root Rhizobacteria Enhances Drought Adaptive Efficacy by Targeting HD-ZIP III Family Genes in Chickpea - Ankita Yadav; Sanoj Kumar; Rita Verma; Shiv Narayan; Uma Gupta; Charu Lata; Shashi Pandey Rai; Indraneel Sanyal (Journal of Soil Science and Plant Nutrition, 2024)

Corrigendum to “Microalgae: A potential bioagent for treatment of emerging contaminants from domestic wastewater” [Chemosphere 351, March 2024, 1–16 141245] - Sanjeet Mehariya; Probir Das; Mahmoud Ibrahim Thaher; Mohammed Abdul Quadir; Shoyeb Khan; Sami Sayadi; Alaa H. Hawari; Pradeep Verma; Shashi Kant Bhatia; Obulisamy Parthiba Karthikeyan; Antonio Zuorro; Hareb Al-Jabri (Chemosphere, 2024)

Microalgae: A potential bioagent for treatment of emerging contaminants from domestic wastewater - Sanjeet Mehariya; Probir Das; Mahmoud Ibrahim Thaher; Mohammed Abdul Quadir; Shoyeb Khan; Sami Sayadi; Alaa H. Hawari; Pradeep Verma; Shashi Kant Bhatia; Obulisamy Parthiba Karthikeyan; Antonio Zuorro; Hareb Al-Jabri (Chemosphere, 2024)

The flight of chicken genomics and allied omics-a mini review - Nidhi Sukhija; K.K. Kanaka; Rangasai Chandra Goli; Palak Kapoor; Jayakumar Sivalingam; Archana Verma; Rekha Sharma; Shashi Bhushan Tripathi; Anoop Anand Malik (Ecological Genetics and Genomics, 2023)

Target cleavage mapping and tissue-specific expression analysis of PGPR responsive miR166 under abiotic stress in chickpea (Cicer arietinum L.) - Ankita Yadav; Sanoj Kumar; Rita Verma; Shashi Pandey Rai; Charu Lata; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Overexpression of PGPR responsive chickpea miRNA166 targeting ATHB15 for drought stress mitigation - Ankita Yadav; Sanoj Kumar; Rita Verma; Shiv Narayan; Ram Jatan; Charu Lata; Shashi Pandey Rai; Pramod A. Shirke; Indraneel Sanyal (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Twenty-two years of precision agriculture: a bibliometric review - Rajshree Misara; Divyanshu Verma; Neha Mishra; Shashi Kant Rai; Saurabh Mishra (Precision Agriculture, 2022)

microRNA 166: an evolutionarily conserved stress biomarker in land plants targeting HD-ZIP family - Ankita Yadav; Sanoj Kumar; Rita Verma; Charu Lata; Indraneel Sanyal; Shashi Pandey Rai (Physiology and Molecular Biology of Plants, 2021)

B-Map: a fuzzy-based model to detect foreign objects in a brain - Dev Baloni; Shashi Kant Verma (Medical & Biological Engineering & Computing, 2021)

Differential expression of apoptosis-associated genes in canine mammary tumors - Namita Mitra; Ramneek Verma; Dipak Deka; Hitesh N. Pawar; Naresh K. Sood; Kuldeep Gupta; Shashi K. Mahajan; Jitender Mohindroo (Biologia, 2015)

Surface energy balance model of transpiration from variable canopy cover and evaporation from residue-covered or bare soil systems: model evaluation - Luis Octavio Lagos; Derrel L. Martin; Shashi B. Verma; Suat Irmak; Ayse Irmak; Dean Eisenhauer; Andrew Suyker (Irrigation Science, 2013)

Estimating seasonal evapotranspiration from temporal satellite images - Ramesh K. Singh; Shuguang Liu; Larry L. Tieszen; Andrew E. Suyker; Shashi B. Verma (Irrigation Science, 2012)

Application of day and night digital photographs for estimating maize biophysical characteristics - Toshihiro Sakamoto; Anatoly A. Gitelson; Brian D. Wardlow; Timothy J. Arkebauer; Shashi B. Verma; Andrew E. Suyker; Michio Shibayama (Precision Agriculture, 2012)

Latitudinal patterns of magnitude and interannual variability in net ecosystem exchange regulated by biological and environmental variables - WENPING YUAN; YIQI LUO; ANDREW D. RICHARDSON; RAM OREN; SEBASTIAAN LUYSSAERT; IVAN A. JANSSENS; REINHART CEULEMANS; XUHUI ZHOU; THOMAS GRÜNWALD; MARC AUBINET; CHRISTIAN BERHOFER; DENNIS D. BALDOCCHI; et al. (Global Change Biology, 2009)
Over the last two and half decades, strong evidence showed that the terrestrial ecosystems are acting as a net sink for atmospheric carbon. However the spatial and temporal patterns of variation in the sink are not well known. In this study, we examined latitudinal patterns of interannual variability (IAV) in net ecosystem exchange (NEE) of CO 2 based on 163 site‐years of eddy covariance data, from 39 northern‐hemisphere research sites located at latitudes ranging from ∼29°N to ∼64°N. We computed the standard deviation of annual NEE integrals at individual sites to represent absolute interannual variability (AIAV), and the corresponding coefficient of variation as a measure of relative interannual variability (RIAV). Our results showed decreased trends of annual NEE with increasing latitude for both deciduous broadleaf forests and evergreen needleleaf forests. Gross primary production (GPP) explained a significant proportion of the spatial variation of NEE across evergreen needleleaf forests, whereas, across deciduous broadleaf forests, it is ecosystem respiration (Re). In addition, AIAV in GPP and Re increased significantly with latitude in deciduous broadleaf forests, but AIAV in GPP decreased significantly with latitude in evergreen needleleaf forests. Furthermore, RIAV in NEE, GPP, and Re appeared to increase significantly with latitude in deciduous broadleaf forests, but not in evergreen needleleaf forests. Correlation analyses showed air temperature was the primary environmental factor that determined RIAV of NEE in deciduous broadleaf forest across the North American sites, and none of the chosen climatic factors could explain RIAV of NEE in evergreen needleleaf forests. Mean annual NEE significantly increased with latitude in grasslands. Precipitation was dominant environmental factor for the spatial variation of magnitude and IAV in GPP and Re in grasslands.

Surface energy balance model of transpiration from variable canopy cover and evaporation from residue-covered or bare-soil systems - Luis Octavio Lagos; Derrel L. Martin; Shashi B. Verma; Andrew Suyker; Suat Irmak (Irrigation Science, 2009)

Linking flux network measurements to continental scale simulations: ecosystem carbon dioxide exchange capacity under non‐water‐stressed conditions - KATHERINE E. OWEN; JOHN TENHUNEN; MARKUS REICHSTEIN; QUAN WANG; EVA FALGE; RALF GEYER; XIANGMING XIAO; PAUL STOY; CHRISTOF AMMANN; ALTAF ARAIN; MARC AUBINET; MIKA AURELA; et al. (Global Change Biology, 2007)
This paper examines long‐term eddy covariance data from 18 European and 17 North American and Asian forest, wetland, tundra, grassland, and cropland sites under non‐water‐stressed conditions with an empirical rectangular hyperbolic light response model and a single layer two light‐class carboxylase‐based model. Relationships according to ecosystem functional type are demonstrated between empirical and physiological parameters, suggesting linkages between easily estimated parameters and those with greater potential for process interpretation. Relatively sparse documentation of leaf area index dynamics at flux tower sites is found to be a major difficulty in model inversion and flux interpretation. Therefore, a simplification of the physiological model is carried out for a subset of European network sites with extensive ancillary data. The results from these selected sites are used to derive a new parameter and means for comparing empirical and physiologically based methods across all sites, regardless of ancillary data. The results from the European analysis are then compared with results from the other Northern Hemisphere sites and similar relationships for the simplified process‐based parameter were found to hold for European, North American, and Asian temperate and boreal climate zones. This parameter is useful for bridging between flux network observations and continental scale spatial simulations of vegetation/atmosphere carbon dioxide exchange.

Linking flux network measurements to continental scale simulations: ecosystem carbon dioxide exchange capacity under non-water-stressed conditions - KATHERINE E. OWEN; JOHN TENHUNEN; MARKUS REICHSTEIN; QUAN WANG; EVA FALGE; RALF GEYER; XIANGMING XIAO; PAUL STOY; CHRISTOF AMMANN; ALTAF ARAIN; MARC AUBINET; MIKA AURELA; et al. (Global Change Biology, 2007)

Enhanced analgesic effect of morphine-nimodipine combination after intraspinal administration as compared to systemic administration in mice - Dilip Verma; Subrata Basu Ray; Ishan Patro; Shashi Wadhwa (Journal of Biosciences, 2005)

Interannual variability in net CO 2 exchange of a native tallgrass prairie - Andrew E. Suyker; Shashi B. Verma; George G. Burba (Global Change Biology, 2003)
Year‐round eddy covariance flux measurements were made in a native tallgrass prairie in north‐central Oklahoma, USA during 1997–2000 to quantify carbon exchange and its interannual variability. This prairie is dominated by warm season C 4 grasses. The soil is a relatively shallow silty clay loam underlined with a heavy clay layer and a limestone bedrock. During the study period, the prairie was burned in the spring of each year, and was not grazed. In 1997 there was adequate soil moisture through the growing season, but 1998 had two extended periods of substantially low soil moisture (with concurrent high air temperatures and vapor pressure deficits), one early and one later in the growing season. There was also moisture stress in 1999, but it was less severe and occurred later in the season. The annual net ecosystem CO 2 exchange, NEE (before including carbon loss during the burn) was 274, 46 and 124 g C m − 2 yr − 1 in 1997, 1998, and 1999, respectively (flux toward the surface is positive), and the associated variation seemed to mirror the severity of moisture stress. We also examined integrated values of NEE during different periods (e.g. day/night; growing season/senescence). Annually integrated carbon dioxide uptake during the daytime showed the greatest variability from year to year, and was primarily linked to the severity of moisture stress. Carbon loss during nighttime was a significant part of the annual daytime NEE, and was fairly stable from year to year. When carbon loss during the burn (estimated from pre‐ and post‐burn biomass samples) was incorporated in the annual NEE, the prairie was found to be approximately carbon neutral (i.e. net carbon uptake/release was near zero) in years with no moisture stress (1997) or with some stress late in the season (1999). During a year with severe moisture stress early in the season (1998), the prairie was a net source of carbon. It appears that moisture stress (severity as well as timing of occurrence) was a dominating factor regulating the annual carbon exchange of the prairie.

Inversion of net ecosystem CO 2 flux measurements for estimation of canopy PAR absorption - Niall P. Hanan; George Burba; Shashi B. Verma; Joseph A. Berry; Andrew Suyker; Elizabeth A. Walter‐Shea (Global Change Biology, 2002)
The fractional absorption of photosynthetically active radiation ( f PAR ) is frequently a key variable in models describing terrestrial ecosystem–atmosphere interactions, carbon uptake, growth and biogeochemistry. We present a novel approach to the estimation of the fraction of incident photosynthetically active radiation absorbed by the photosynthetic components of a plant canopy ( f Chl ). The method uses micrometeorological measurements of CO 2 flux and incident radiation to estimate light response parameters from which canopy structure is deduced. Data from two Ameriflux sites in Oklahoma, a tallgrass prairie site and a wheat site, are used to derive 7‐day moving average estimates of f Chl during three years (1997–1999). The inverse estimates are compared to long‐term field measurements of PAR absorption. Good correlations are obtained when the field‐measured f PAR is scaled by an estimate of the green fraction of total leaf area, although the inverse technique tends to be lower in value than the field measurements. The inverse estimates of f Chl using CO 2 flux measurements are different from measurements of f PAR that might be made by other, more direct, techniques. However, because the inverse estimates are based on observed canopy CO 2 uptake, they might be considered more biologically relevant than direct measurements that are affected by non‐physiologically active components of the canopy. With the increasing number of eddy covariance sites around the world the technique provides the opportunity to examine seasonal and inter‐annual variation in canopy structure and light harvesting capacity at individual sites. Furthermore, the inverse f Chl provide a new source of data for development and testing of f PAR retrieval using remote sensing. New remote sensing algorithms, or adjustments to existing algorithms, might thus become better conditioned to ‘biologically significant’ light absorption than currently possible.

Year‐round observations of the net ecosystem exchange of carbon dioxide in a native tallgrass prairie - Andrew E. Suyker; Shashi B. Verma (Global Change Biology, 2001)
Summary An Ameriflux site was established in mid 1996 to study the exchange of CO 2 in a native tallgrass prairie of north‐central Oklahoma, USA. Approximately the first 20 months of measurements (using eddy covariance) are described here. This prairie, dominated by warm season C4 grasses, is typical of the central Kansas/northern Oklahoma region. During the first three weeks of the measurement period (mid‐July–early August 1996), moisture‐stress conditions prevailed. For the remainder of the period (until March 1998), however, soil moisture was nonlimiting. Mid‐day net ecosystem CO 2 exchange (NEE), under well‐watered conditions, reached a maximum magnitude of 1.4 mg CO 2 m −2 s −1 (flux toward the surface is positive) during peak growth (mid‐July 1997), with green leaf area index of 2.8. In contrast, under moisture‐stress conditions in the same growth stage in 1996, mid‐day NEE was reduced to near‐zero. Average night NEE ranged from near‐zero, during winter dormancy, to − 0.50 mg CO 2 m −2 s −1 , during peak growth. Most of the variance in average night NEE was explained by changes in soil temperature (0.1 m depth) and green leaf area. The daytime NEE measurements were examined in terms of a rectangular hyperbolic relationship with incident photosynthetically active radiation. The analysis showed that the quantum yield during peak growth was similar to those measured in other prairies and the y ‐intercept, so obtained, can be potentially used as an estimate of night‐time CO 2 emissions when eddy covariance data are unavailable. Daily integrated NEE reached its peak magnitude of 30.8 g CO 2 m −2 d −1 (8.4 g C m −2 d −1 ) in mid‐July when the green LAI was the largest (about 2.8). In general, the seasonal trend of daily NEE (on relatively clear days) followed that of green LAI. Annually integrated carbon exchange, between prescribed burns in 1997 and 1998, was 268 g C m −2 y −1 . After incorporating carbon loss during the prescribed burn , the net annual carbon exchange in this prairie was near‐zero in 1998.

A comparative study of surface energy fluxes of three communities (Phragmites australis, Scirpus acutus, and open water) in a prairie wetland ecosystem - George G. Burba; Shashi B. Verma; Joon Kim (Wetlands, 1999)

Seasonal variation in methane emission from a temperate Phragmites‐dominated marsh: effect of growth stage and plant‐mediated transport - JooN. Kim; Shashi B. Verma; David P. Billesbach (Global Change Biology, 1999)
The eddy covariance technique was employed with a tunable diode laser spectrometer to quantify methane flux from a prairie marsh dominated by Phragmites australis in north‐central Nebraska, USA. The observations spanned the entire growing season (April to October) and a wide range of weather conditions, allowing a quantitative assessment of the physical and biological controls of methane emission in this ecosystem. Diel patterns in methane emission varied markedly depending on plant growth stage. Prior to plant emergence above water, the rate of methane emission from the marsh was fairly constant throughout the day. After emergence above water, there was a gradual increase in methane emission after sunrise with a peak in late afternoon. Significant changes in diel patterns were observed after tillering. Then, the diel pattern was characterized by a mid‐ to late‐morning peak and a 2‐to 4‐fold increase in methane emissions from night to daytime. In early stages of plant growth, molecular diffusion through dead/live plants and the standing water column seemed to be the primary transport mechanism. After tillering, a transition occurred in the transport mechanism from a molecular diffusion to a convective throughflow, which is a rapid and active gas transport driven by pressure differences. The role of convective throughflow became less important as the plants senesced. Integrated methane emission over the six‐month measurement period (April–October) was about 64 g CH 4 m –2 . On an annual basis, we estimate the annual methane emission from this ecosystem to be ≈ 80 g CH 4 m –2 and that about 80% of the total methane emission occurred between late April and late October.